PENGEMBANGAN BAHAN AJAR PERKALIAN DAN PEMBAGIAN DENGAN MENGADOPSI OPERASI ARITMATIKA BANGSA MESIR KUNO - Attin Warmi (Universitas Majalengka, 2020)
This program is one of the community service programs carried out by groups of lecturers and student representatives of the mathematics education program at UNSIKA. This program is in the form of providing tutoring outside school hours to elementary school students in mathematics. Most students are of the view that mathematics is difficult. Based on these conditions, we will design a program to help the school in providing tutoring to students in dealing with students to facilitate learning multiplication and division. The form of the program is in the form of providing tutoring for elementary school students, to facilitate student learning in completing multiplication and division operations. For the implementation of this activity, the mathematics textbooks and modules that are designed for guidance and study must be prepared. The material to be applied is about mathematical materials that have been summarized relating to multiplication and division operations. The structure of teaching materials for each topic starts with concepts, examples of questions, exercises, discussions and key answers. The textbook is ready to be used for the program.